Assessing highway slope stability risks using InSAR: a case study in Bijie, China - Liyuan Duan; Hwee San Lim; Sya’rawi Muhammad Husni Mohd Sharoni; Meili Chen; Nana Han; Xuejun Tian (Geocarto International, 2025)
Road networks are important for promoting economic development. Once roads are put into use, regular monitoring of slope and surrounding deformation is vital to prevent disasters. This study evaluates the effectiveness of differential interferometric synthetic aperture radar (DInSAR) and time series InSAR (TS-InSAR) techniques for detecting slope deformation along highways in Bijie City, China, from March 2020 to November 2021. A total of 107 C-band Sentinel-1A images and 4 L-band ALOS-2 images were used to identify 52 deformation points. After excluding 21 deformation points distant from highways, field verification of the remaining 31 points confirmed 26 highway-related geological hazards. The results demonstrate the capability of InSAR to detect geological hazards along highways, reducing monitoring costs by 60% compared with traditional methods. However, it should be noted that while InSAR significantly significantly lowers costs and improves coverage, it should integrate with ground-based observations to ensure comprehensive, accurate, and real-time hazard assessment..